(3fRgI GdfXGQ hQhVI GdCTYGQs ((3EHQGgje GdYeGQ s)
(3ChdgG (B:s
(3GdMeO ddg LGeY Gdcde GdWjH hefRd GdYPH GdRdGd GdUjH aChd eG jHJOC ai gPG GdcJGH cdGe ef CYdi Gddg OQLJg ai GdeBH SjOi GdTjN eMi GdOji YHO GdbGOQ GdLjdGfi s
(3BNQgG (B:s
(3GdMeO ddg NGdb Hfi COe ef GdeGA hGdWjf haVdg Ydi SGFQ GdCTjGA hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3eNJGQGJ ef TYQ GdUhajIs
(3jTJed Ydi cdGe GdChdjGA hGdUGdMjfs
(3ef cdGe GdTjN YHO GdbGOQ GdLHdi hGHf haG h SjOi CHh GdaVd Hf haGs
(3hfLe GdOjf Hf ESQGFjd hTeS GdOjf Hf GdYaja hYQbdI GdOeTbi s
(3hGdHgGA RgjQ s
(3hGHf fHGJI GdeUQi HBNQg eWGdYIaQZ GdeDd s
Keywords: (3GdJUha hGdBOGH GdTQYjIs